2014
DOI: 10.1177/1553350614525670
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Smartphone Applications Across Different Platforms

Abstract: Despite the plethora of surgical applications available for smartphones, there is no taxonomy for medical applications. Only 12% were affiliated with an academic institution or association, which highlights the need for greater regulation of surgical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…Recent estimates anticipate over 500 million users applying smartphones in health-care related contexts by 2015 [4] with a steadily increasing availability [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates anticipate over 500 million users applying smartphones in health-care related contexts by 2015 [4] with a steadily increasing availability [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Many applications useful to the plastic surgeons are not found when searching "plastic surgery" in the app stores. [9][10][11][12][13][14][15] These apps were often listed in previous literature reviews or found by searching very specific terms (eg, percent burn calculator).…”
Section: Discussionmentioning
confidence: 99%
“…9-14 These apps were not included. Compared with a similar search conducted in 2013 by Kulendran et al, 9 there were a total of 203 apps on the iOS store and 140 apps on Google Play excluding game and photo apps (62% increase and 580% increase, respectively). When reviewing the apps for practice development, 125 apps were identified on the iOS and 59 on Google Play.…”
Section: Application Store Searchmentioning
confidence: 95%
“…The FDA only regulates those apps that provide direct medical advice [1••]. An analysis of all currently available medical apps revealed that only 12 % are associated with an academic institution or association, stressing the need for further regulation [13].…”
Section: Introductionmentioning
confidence: 99%